Optimizing Crop Monitoring Efficiency and Precision with Drone Technology - , Narinder Panotra; , D.M. Kadam; , Amrith Raj; , Dileep Kumar G D; , Lalita Kumar Mohanty; , Rayees A Wani; , Bhim Singh; , Chandan Kumar Panigrahi; , Shabnam Kundal; , Vijay Kumar; , Bal Veer Singh (Archives of Current Research International, 2025)
Drone technology has emerged as a powerful tool for enhancing crop monitoring efficiency and precision in modern agriculture. This review article explores the applications, benefits, and challenges of using drones for crop monitoring. Drones equipped with various sensors and imaging capabilities enable farmers to collect high-resolution data on crop health, growth, and stress factors. The integration of drone-based monitoring systems with precision agriculture practices allows for targeted interventions, optimized resource management, and improved crop yields. However, the adoption of drone technology in agriculture faces challenges such as high costs, regulatory constraints, and data processing complexities. This article provides insights into the current state of drone-based crop monitoring, its potential for revolutionizing agricultural practices, and future research directions to overcome existing limitations. By harnessing the power of drone technology, farmers can make data-driven decisions, reduce input costs, and enhance the sustainability and profitability of their farming operations.